Downregulation of lncRNA PVT1 expression inhibits proliferation and migration by regulating p38 expression in prostate cancer - Wan, Bo (Oncol Lett, 2018)
Long non-coding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) has been reported to be overexpressed in prostate cancer cells and associated with tumorigenesis in various types of cancer. However, the biological function of lncRNA PVT1 remains largely unknown. The aim of the present study was to investigate the effect of lncRNA PVT1 expression on the proliferation and migration of prostate cancer cells. Stably transfected prostate cancer cells with downregulated expression of lncRNA PVT1 were constructed by an efficient siRNA fragment, followed by confirmation by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Proliferation was assessed using CCK-8, colony formation and xenograft assays, and cell migration was evaluated using a wound healing assay. The PathScan(®) Intracellular Signaling Array kit was utilized to explore the underlying molecular mechanisms of lncRNA PVT1 expression in prostate cancer cells. RT-qPCR results confirmed that the lncRNA PVT1 expression level was successfully knocked down in prostate cancer cells. When lncRNA PVT1 expression was downregulated in prostate cancer cells, proliferation and migration were significantly inhibited, compared with the control lncRNA PVT1 group. Furthermore, PVT1 knockdown decreased the phosphorylation of p38 in DU145 cells. Therefore, the present study demonstrated that lncRNA PVT1 downregulation inhibits the proliferation and migration of prostate cancer cells, and is associated with p38 phosphorylation.